2011
DOI: 10.1111/j.1540-6261.2010.01637.x
|View full text |Cite
|
Sign up to set email alerts
|

Public Information and Coordination: Evidence from a Credit Registry Expansion

Abstract: This paper provides evidence that lenders to a firm close to distress have incentives to coordinate: lower financing by one lender reduces firm creditworthiness and causes other lenders to reduce financing. To isolate the coordination channel from lenders' joint reaction to new information, we exploit a natural experiment that forced lenders to share negative private assessments about their borrowers. We show that lenders, while learning nothing new about the firm, reduce credit in anticipation of other lender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
83
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(92 citation statements)
references
References 65 publications
8
83
1
Order By: Relevance
“…In addition, when the extra positive information of a borrower is shared to the bank, the extra negative information is not important anymore. We do not find evidence for the "publicity multiplier" of information as documented by Hertzberg et al (2008) for Argentina; however, we find that the bank lowers its credit card supply to borrowers who carry greater credit card balances at other banks. Our results thus are in line with Bennardo et al (2009) where multiple lending relationships induce banks to ration credit, for fear that the borrower's total exposure may become so large as to induce default; however, when banks share information about their seniority or/and about their loan sizes, lending becomes safer, and credit rationing is reduced.…”
mentioning
confidence: 45%
See 1 more Smart Citation
“…In addition, when the extra positive information of a borrower is shared to the bank, the extra negative information is not important anymore. We do not find evidence for the "publicity multiplier" of information as documented by Hertzberg et al (2008) for Argentina; however, we find that the bank lowers its credit card supply to borrowers who carry greater credit card balances at other banks. Our results thus are in line with Bennardo et al (2009) where multiple lending relationships induce banks to ration credit, for fear that the borrower's total exposure may become so large as to induce default; however, when banks share information about their seniority or/and about their loan sizes, lending becomes safer, and credit rationing is reduced.…”
mentioning
confidence: 45%
“…2 Others find that private credit bureaus, rather than public credit registries, are associated with lower perceived financing constraints and a higher share of bank financing (Love and Mylenko (2003)), or that the lowering of reporting thresholds of a public credit registry results in lower lending to firms that had multiple lending relationships (Hertzberg et. al (2008)).…”
Section: Introductionmentioning
confidence: 99%
“…Information sharing is useful if borrower mobility is higher (Pagaon and Jappelli, 1993) and if asymmetric information problems are more important (Brown and Zehnder, 2010). Empirical research has shown that, information sharing is correlated with higher access to credit (Pagaon and Jappelli, 1993), especially in developing countries with inefficient creditor rights (Djankov et al, 2007), but lower lending to low-quality borrowers (Hertzberg et al, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This could happen, for example, if the outside loans facilitate a worthwhile project that the initial creditor could not finance alone (e.g., due to lack of sufficient liquidity as in Detragiache et al (2001) or a too large exposure to the borrower as in Hertzberg et al (2011)). 10 In sharp contrast with H1, an outside loan in this case should increase the initial creditor's willingness to lend and it should increase it more the larger the outside loan.…”
Section: Hypotheses On the Impact Of Non-exclusivity In Financial Conmentioning
confidence: 99%